SYSTOLIC AUTOMATED OFFICE BP (AOBP), WITH NURSE ABSENT, COMPARED TO OTHER CLINIC BP MEASUREMENTS. (June 2018) - Chang, A.; Andreadis, E.; Tsioufis, K.; Geladari, C.; Papademetriou, V.
Abstract : Objective: To compare differences between systolic AOBP measured without the presence of a nurse with other oscillometric and auscultatory OBP measurement taken by a nurse or a physician. Figure. No caption available. Design and method: We prospectively evaluated 55 hypertensive patients seen in the Hypertension clinic of the Washington DC VA Medical Center, mean age 68 ± 13 years, 10 women. Four types of BP measurements were obtained; (i) AOBP measurements, using the fully automated Omron-HEM 907 sphygmomanometer with the nurse out of the exam room (ii) Oscilometric office BP (OBP) taken by a nurse, using a validated digital oscillometric BP electronic device (Dinamap), (iii) OBP taken by a physician, using the same validated osciometric device and (iv) Auscultatory OBP measurements taken by the same physician. Appropriate cuff size was used in all cases. AOBP readings were programmed to start after 5 minute wait and to record 3 BP readings at one-minute intervals. Participants were alone during the five-minute resting period and the three measurements. All other OBP measurements were also taken in triplicates and the average was calculated. Subjects remained seated for five minutes, before OBP was measured, and were asked to refrain from speaking during measurements. Of note, the nurse and the physicians from the study team were blinded to each other's BP measurements. Continuous variables are reported as mean ± SD. Frequencies are described as percentages. We evaluated agreement between methods by using the method of Bland and Altman. A calculated difference of p < 0.05 was considered to be statistically significant. We used SPSS version 22.0 for data analysis. Results: Mean AOBP values averaged 135/75 mmHg, the oscillometric nurse and physician OBPs averaged 145/75mHg (P < 0.001), and 142/78 mmHg (P < 0.001) respectively and the physician auscultatory measurement averaged 140/77 mmHg (P = NS). Bland-Altman plots with bias and 95% limits of agreement for systolic AOBP (with nurse absent) and other systolic conventional OBP measurements are given in Figures 1–3. Conclusions: High quality AOBP measurements are lower than other conventional OBP readings, suggesting AOBP may be eliminating some of the white-coat effect in everyday clinical practice.